STRATEGIES FOR INTEGRATING CHARACTER EDUCATION INTO SCIENCE LEARNING TO PROMOTE ACADEMIC ACHIEVEMENT AMONG STUDENTS AT SMA NEGERI 1 MANIAMOLO - Harefa, Darmawan (TUNAS : Jurnal Pendidikan Biologi, 2024)
This study aims to examine the impact of integrating character values into science learning on students' attitudes, behavior, motivation, and academic achievement. Through holistic and contextual approaches, values such as honesty, responsibility, and discipline are internalized at every stage of the learning process. The findings indicate that this approach not only enhances students' understanding of scientific concepts but also fosters positive scientific attitudes, such as honesty during experiments, collaboration in group discussions, and concern for environmental issues. Observations of student behavior revealed an increase in responsibility and active engagement throughout the learning process. Furthermore, students' learning motivation significantly improved as they found the learning experience more meaningful and relevant to their daily lives. Academically, there was a noticeable increase in the average evaluation scores in science subjects following the implementation of this strategy. These findings support the importance of developing science learning models that emphasize not only cognitive aspects but also character formation as an integral part of 21st-century education. Character-based science education has proven to be effective in improving the overall quality of education.